Use of access control to minimise ransomware impact. Issue 7 (July 2017) - Parkinson, Simon
Abstract : The potential for financial gain has resulted in the establishment of a multi-billion dollar ransomware industry founded on exploitation. 1 Those with weak, unprotected systems, as well as those with little security-specific knowledge, are more likely to fall victim. Such users may not be able to adequately assess the potential risks and may be caught unaware. Those with the most to lose – for example, users who are heavily reliant on their IT system and its data for undertaking their daily business – heighten the potential for exploitation. Ransomware is now a multi-billion dollar industry. Those with weak, unprotected systems, as well as those with little security-specific knowledge, are most likely to fall victim. Such users may not be able to adequately assess the potential risks. And those with the most to lose – for example, users who are heavily reliant on their IT system and its data for undertaking their daily business – heighten the potential for exploitation. Simon Parkinson of the University of Huddersfield examines how access tools can be used to reduce the threat from ransomware.